Perspectives on punishment: the contours of control - Armstrong, Sarah (Oxford Univ. Press, 2006)
Audiences, borders, architecture : the contours of control / Sarah Armstrong and Lesley McAra -- Ordinary anxieties and states of emergency : statecraft and spectatorship in the new politics of insecurity / Richard Sparks -- Tony Martin and the nightbreakers : criminal law, victims, and the power to punish / Lindsay Farmer -- European identity, penal sensibilities, and communities of sentiment / Evi Girling -- Penalization, depoliticization, racialization : on the over-incarceration of immigrants in the European Union / Loi͏̈c Wacquant -- Prisons during transition : promoting a common penal identity through international norms / Laura Piacentini -- Lex vigilatoria : towards a control system without a state? / Thomas Mathiesen -- Welfare and punishment in comparative perspective / David Downes and Kirstine Hansen -- Sentencing as a social practice / Neil Hutton -- 'Architecture', criminal justice, and control / Richard Jones -- Power, social control, and psychiatry : some critical reflections / Andrew Scull -- Origins of actuarial justice / Malcolm Feeley